On the Origin of Radial Anisotropy Near Subducted Slabs in the Midmantle. (16th November 2019) - Sturgeon, William; Ferreira, Ana M.G.; Faccenda, Manuele; Chang, Sung‐Joon; Schardong, Lewis
Abstract: Recent seismic studies indicate the presence of seismic anisotropy near subducted slabs in the transition zone and uppermost lower mantle (mid‐mantle). In this study, we investigate the origin of radial anisotropy in the mid‐mantle using 3‐D geodynamic subduction models combined with mantle fabric simulations. These calculations are compared with seismic tomography images to constrain the range of possible causes of the observed anisotropy. We consider three subduction scenarios: (i) slab stagnation at the bottom of the transition zone; (ii) slab trapped in the uppermost lower mantle; and (iii) slab penetration into the deep lower mantle. For each scenario, we consider a range of parameters, including several slip systems of bridgmanite and its grain‐boundary mobility. Modeling of lattice‐preferred orientation shows that the upper transition zone is characterized by fast‐SV radial anisotropy anomalies up to −1.5%. For the stagnating and trapped slab scenarios, the uppermost lower mantle is characterized by two fast‐SH radial anisotropy anomalies of ∼+2% beneath the slab's tip and hinge. On the other hand, the penetrating slab is associated with fast‐SH radial anisotropy anomalies of up to ∼+1.3% down to a depth of 2, 000 km. Four possible easy slip systems of bridgmanite lead to a good consistency between the mantle modeling and the seismic tomography images: [100](010), [010](100), [001](100), and < 110 > { 1 ¯ 10 } . The anisotropy anomalies obtained from shape‐preferred orientation calculations do not fit seismic tomography images in the mid‐mantle as well as lattice‐preferred orientation calculations, especially for slabs penetrating into the deep lower mantle. Plain Language Summary: Seismology studies reveal that subducting slabs show different characteristics across the Earth; some flatten in the upper mantle (at 660‐km depth), others are trapped in the uppermost lower mantle (660‐ to 1, 200‐km depth), and a few penetrate into the deep lower mantle. Subducting slabs cause the surrounding mantle to deform, but the way in which the minerals deform in the mid‐mantle (410‐ to 1, 200‐km depth) remains poorly understood. Geodynamic modeling can help us to infer how the mantle flows and deforms around subduction zones. However, the pattern and evolution of mantle flow around the full range of subduction scenarios has yet to be studied in such detail. Therefore, in this study, geodynamic modeling is used to explore a range of mid‐mantle parameters that best fit observations around subduction zones from seismology studies. Deformation in the mid‐mantle induced by subducting slabs, including deeply penetrating slabs, is found to be consistent with a mechanism known as dislocation creep, which involves the movement of defects in the crystal lattice of rocks in the deep Earth, and agrees with recent seismic, geodynamic, and laboratory studies. Key Points: Geodynamical modeling of anisotropy around slabs shows V S V > V S H in the transition zone and V S H > V S V in the topmost lower mantle Shape‐preferred orientation calculations do not fit seismic observations well, notably for deeply penetrating slabs Four possible easy slip systems of bridgmanite are found, agreeing with recent laboratory experiments